2019
DOI: 10.3390/ani9100848
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Chemerin on Autophagy and Apoptosis in Dairy Cow Mammary Epithelial Cells

Abstract: Simple SummaryThe process of mammary gland involution during the early is accomplished by both apoptosis and autophagy. Chemerin, a novel adipocytokine, plays a pivotal role in immune response and lipid metabolism, which was involved in the regulation of programmed cell death. This study focused on the relationship between autophagy and apoptosis in the presence of Chemerin in bovine mammary epithelial cells (BMECs). The results indicated that Chemerin could activate the complete autophagy process and induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Our study confirms that chemerin induces cementoblast apoptosis, as demonstrated by the increased level of cleaved caspase 3 and the increased number of apoptotic cells detected by flow cytometry in chemerin‐treated cells compared with control cells. This conclusion is consistent with the findings of other studies showing that chemerin can induce apoptosis in other kinds of cells 24,25 . The results of the CCK‐8 assay showed fold increases in relative cell number in the chemerin‐treated group compared with the unstimulated control group at 12 hours.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirms that chemerin induces cementoblast apoptosis, as demonstrated by the increased level of cleaved caspase 3 and the increased number of apoptotic cells detected by flow cytometry in chemerin‐treated cells compared with control cells. This conclusion is consistent with the findings of other studies showing that chemerin can induce apoptosis in other kinds of cells 24,25 . The results of the CCK‐8 assay showed fold increases in relative cell number in the chemerin‐treated group compared with the unstimulated control group at 12 hours.…”
Section: Discussionsupporting
confidence: 92%
“…This conclusion is consistent with the findings of other studies showing that chemerin can induce apoptosis in other kinds of cells. 24,25 The results of the CCK-8 assay showed fold increases in relative cell number in the chemerin-treated group compared with the unstimulated control group at 12 hours. No significant differences were observed at 24 or 48 hours, indicating that chemerin did not exhibit cytotoxicity in OCCM-30 cells at the doses and durations used.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, macrophages are recruited to remove apoptotic cells, resulting in the occupation of stromal cells in tissue [ 25 ]. Additionally, Hu et al reported that chemerin induced the activities of autophagy and apoptosis in cultured bovine mammary epithelial cells (BMECs) [ 26 ]. The chemerin-induced apoptosis was further activated when autophagy was inhibited by chloroquine.…”
Section: Discussionmentioning
confidence: 99%
“…The chemerin-induced apoptosis was further activated when autophagy was inhibited by chloroquine. This implicates that chemerin can induce the programmed death of bovine mammary epithelial cells during the process of involution and maintenance of the mammary gland during the dry-off period [ 26 ]. Therefore, chemerin was suggested to act as a chemokine to antigen-presenting cells (APCs), and also as an inducer of apoptosis in involuting/involuted mammary glands, which supports the closed relationship between chemerin and the immune response in mammary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Aβ42 stimulates CMKLR1-RBL cells and primary glial cells to internalize the Aβ42-CMKLR1 complex, which helps in the clearance of Aβ42 (Kulig et al, 2011). Very recently, chemerin was reported to induce autophagy in bovine mammary epithelial cells (Hu et al, 2019). Therefore, it is reasonable to speculate that it might induce autophagy in microglial cells also, which needs to be explored.…”
Section: Chemokines Chemerinmentioning
confidence: 99%